PERFORMANCE INDEX AND OPERATING RATIO: EFFECTS ISLAMIC ON SHARIA PROFITABILITY IN INDONESIA - Ajeng Tita Nawangsari; Mochammad Ilyas Junjunan; Zakiyatul Fakhiroh; Ana Toni Roby Candra Yudha; Achmad Room Fitrianto (JRAK, 2022)
This study aimed to to ascertain the impact of Islamic Performance Index and Operating Efficiency Ratio on the financial performance of Islamic banking for 2016-2020 period. Purposive sampling was used as the empirical methodology. Data analysis was done by using Eviews 12 software and moderated regression analysis (MRA). The findings indicated that while the Islamic income ratio did not have impact on profitability, the profit sharing ratio and operating efficiency ratio had a significant detrimental impact on it. The findings also showed that intellectual capital can influence profitability by reducing the impact of operating efficiency ratio and profit sharing ratio, but it cannot affect profitability by reducing the impact of Islamic income ratio.